Piattaforme, mediazione e rappresentazione: regimi di visibilità e di verità nei dispositivi digitali - Cuoco, Giacomo (B@belonline, 2022)
The aim of this contribution is understanding digital platforms, whose structure has now infected almost all the space of the web, as devices aimed at reproducing specific profit- and control-oriented capitalist operations. Such understanding implies the critical demystification of a widespread vision of internet that presents it as a transparent and immediate environment that grants a limitless vision and access to information. On the contrary, building on the intuitions of Foucault and Deleuze, the consideration of the platform as a dispositif allows to show the regimes of visibility and enunciation that it arranges, to reveal the epistemological basis and the specific regime of truth it imposes – as well as to convert transparency into opacity and immediacy into hyper-mediation.